A novel quantitative real-time PCR diagnostic assay for seal heartworm (Acanthocheilonema spirocauda) provides evidence for possible infection in the grey seal (Halichoerus grypus). Issue 2 (August 2018) - Keroack, Caroline D.; Williams, Kalani M.; Fessler, M.K.; DeAngelis, Kaela E.; Tsekitsidou, Eirini; Tozloski, Jillian M.; Williams, Steven A.
Abstract: The distinct evolutionary pressures faced by Pinnipeds have likely resulted in strong coevolutionary ties to their parasites (Leidenberger et al., 2007). This study focuses on the phocid seal filarial heartworm species Acanthocheilonema spirocauda . A. spirocauda is known to infect a variety of phocid seals, but does not appear to be restricted to a single host species (Measures et al., 1997; Leidenberger et al., 2007; Lehnert et al., 2015). However, to date, seal heartworm has never been reported in grey seals ( Halichoerus grypus ) (Measures et al., 1997; Leidenberger et al., 2007; Lehnert et al., 2015). The proposed vector for seal heartworm is Echinophthirius horridus, the seal louse. Seal lice are known to parasitize a wide array of phocid seal species, including the grey seal. With the advent of climate change, disease burden is expected to increase across terrestrial and marine mammals (Harvell et al., 2002). Accordingly, increased prevalence of seal heartworm has recently been reported in harbor seals ( Phoca vitulina ) (Lehnert et al., 2015). Thus, the need for improved, rapid, and cost-effective diagnostics is urgent. Here we present the first A. spirocauda- specific rapid diagnostic test (a quantitative real-time PCR assay), based on a highly repetitive genomic DNA repeat identified using whole genome sequencing and subsequent bioinformatic analysis. The presence of an insect vector provides the opportunity to develop a multifunctional diagnostic tool that can be used not only to detect the parasite directly from blood or tissue specimens, but also as a molecular xenomonitoring (XM) tool that can be used to assess the epidemiological profile of the parasite by screening the arthropod vector. Using this assay, we provide evidence for the first reported case of seal heartworm in a grey seal. Graphical abstract: Image 1 Highlights: A novel real-time PCR diagnostic for seal heartworm ( Acanthocheilonema spirocauda ) is developed and presented. The diagnostic is applicable to use on whole parasite specimens, xenomonitoring, and blood samples. This diagnostic is used to detect the evidence of seal heartworm in the grey seal ( Halichoerus grypus ).